2023
DOI: 10.1021/acs.jproteome.2c00595
|View full text |Cite
|
Sign up to set email alerts
|

Onto Grid Purification and 3D Reconstruction of Protein Complexes Using Matrix-Landing Native Mass Spectrometry

Abstract: Addressing mixtures and heterogeneity in structural biology requires approaches that can differentiate and separate structures based on mass and conformation. Mass spectrometry (MS) provides tools for measuring and isolating gas-phase ions. The development of native MS including electrospray ionization allowed for manipulation and analysis of intact noncovalent biomolecules as ions in the gas phase, leading to detailed measurements of structural heterogeneity. Conversely, transmission electron microscopy (TEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…As the structural impact is expected to be larger the higher the electric field, our study also show that in MS and other techniques where EFs are applied to manipulate proteins, protein structures are likely to be virtually unaffected by the EFs if the latter are weaker or comparable to field strengths investigated herein. This corroborates recent observations from soft-landing experiments, where native MS is used to select specific proteins and deposit them on surfaces that are later used for electron microscopy[72,73,74,75]. The resolution of such experiments have not allowed for atomistic structures, but it is clear that the overall shape of the proteins remain intact under the right condition, even after much longer dehydration times than in our vacuum simulations.…”
supporting
confidence: 90%
“…As the structural impact is expected to be larger the higher the electric field, our study also show that in MS and other techniques where EFs are applied to manipulate proteins, protein structures are likely to be virtually unaffected by the EFs if the latter are weaker or comparable to field strengths investigated herein. This corroborates recent observations from soft-landing experiments, where native MS is used to select specific proteins and deposit them on surfaces that are later used for electron microscopy[72,73,74,75]. The resolution of such experiments have not allowed for atomistic structures, but it is clear that the overall shape of the proteins remain intact under the right condition, even after much longer dehydration times than in our vacuum simulations.…”
supporting
confidence: 90%
“…The following DC gradient was placed on the ion optics from the inlet of the mass spectrometer to the TEM grid: Source DC offset 0 V, injection flatapole 1 V, inter flatapole lens 1 V, bent flatapole 1 V, transfer multipole 1 V, C-trap entrance lens 0 V, HCD field gradient 0 V, HCD cell DC offset −4.5 V, HCD cell exit lens 0 V, and TEM grid −1 V. A wide mass filter isolation of 8000–18,000 m / z was employed. Note that, though not the focus of this study, this same setup could be used to purify complexes, as we have recently published . Proteins were landed on ultrathin carbon over lacy carbon grids (CLC400Au25-UT, EM Resolutions, UK), which were first glow discharged for 30 s.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Despite these challenges, considerable efforts toward the goal of coupling MS with cryo-EM are being made by several laboratories. For example, using a modified Orbitrap system for landing cations of protein–protein complexes, we found that particles deposited onto carbon grids lacked the structural quality to enable 3D reconstructions. We solved this problem by using a chemical landing matrix that preserves the deposited particles so that their 3D structures could be solved to the resolution of negative-stain TEM (∼20 A). In fact, the structures of the landed particles were virtually identical to those prepared conventionally.…”
Section: Introductionmentioning
confidence: 99%
“…Because the nMS instrument tuning parameters are critical for analyzing weak interactions, this requires experienced researchers and/or operators with strong fundamental knowledge of nMS and allied MS techniques such as CID, ECD, and IM in order to generate high-quality, reproducible data and for a rich interpretation of the significant detail present within the nMS mass spectra. Additionally, as new hyphenated MS techniques develop (e.g., MS-cryoEM is on the horizon ), very powerful combinations of biophysical methods that can be utilized for TPD are envisaged. Because nMS is well developed for fragment screening, , and fragment sized starting points are arguably better as E3 recruiter ligands and/or POI ligands, it is conceivable that nMS could also play a strong role in identifying novel E3 recruiter ligands by screening fragment libraries.…”
Section: Future Insights and Opportunities For Nms With Targeted Prot...mentioning
confidence: 99%